Effect of hydroxyapatite nanoparticles on enamel remineralization and estimation of fissure sealant bond strength to remineralized tooth surfaces: an in vitro study - Mahtab Memarpour; Fereshteh Shafiei; Azade Rafiee; Mina Soltani; Mohammad Hossein Dashti (BMC, 2019)
Abstract Background The management of noncavitated caries lesions before sealant therapy is a clinical challenge when the tooth needs sealant application. Sealing noncavitated carious lesions in pits and fissures may lead to failure of the fissure sealant (FS) due to incomplete sealing. Therefore the use of remineralizing agents such as nanoparticles has been suggested. This study investigated the ability of hydroxyapatite nanoparticles (nano-HA) to remineralize enamel, and their effect on sealant microleakage and shear bond strength (SBS). Methods A total of 192 third molars were demineralized and pretreated with two concentrations of nano-HA with and without sodium hexametaphosphate (SHMP), followed by phosphoric acid etching and resin FS application. The study groups were 1) etching + FS, 2) etching + nano-HA 0.15% + FS, 3) etching + nano-HA 0.03% + FS, 4) etching + mixture of nano-HA 0.15% and SHMP 0.05% + FS, 5) etching + mixture of nano-HA 0.03% + SHMP 0.01% + FS. The laboratory tests included microleakage in 50 teeth, scanning electron microscopy (SEM) evaluation in 10 samples, and SBS in 100 samples. Enamel remineralization changes were evaluated in 32 teeth with energy-dispersive X-ray spectroscopy (EDS) and field emission scanning electron microscope (FESEM). Results Nano-HA enhanced the SBS to remineralized enamel in a large percentage of nanoparticles. Mean SBS in group 2 was significantly greater than in groups 1, 3 and 4 (all P < 0.05). SBS was related to nano-HA concentration: nano-HA 0.15% yielded greater SBS (16.8 ± 2.7) than the 0.03% concentration (14.2 ± 2.1). However, its effect on microleakage was not significant. Nano-HA with or without SHMP led to enhanced enamel remineralization; however, the Calcium (Ca)/Phosphate (P) weight percent values did not differ significantly between the groups (P > 0.05). SEM images showed that SHMP did not affect sealant penetration into the deeper parts of fissures. FESEM images showed that adding SHMP led to increased nanoparticle dispersal on the tooth surface and less cluster formation. Conclusions The ultraconservative approach (combining nano-HA 0.15% and SHMP) and FS may be considered a minimal intervention in dentistry to seal demineralized enamel pits and fissures.